Laser cladding double-layer structure wear-resistant coating and preparation method thereof
Through the use of laser melting technology on the 316L stainless steel substrate to prepare double -layer structured wear -resistant coating, medium entropy coating as the bottom layer and high entropy coating as the top layer, solve the high entropy coating and stainless steel substrate due to thermal expansion coefficient and physical chemistry The cracking problem caused by high performance differences realizes the high -wear resistance, corrosion resistance performance and the hardness of the matrix in the coating.
Patent Information
- Application Number
- CN202411355276.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-24
AI Technical Summary
Due to the large difference between the thermal expansion coefficient and physical and chemical properties of the high-entropy coating and the 316L stainless steel matrix, cracks or cracks are easily formed on the surface of the high-entropy coating after cladding.
Laser cladding technology is used to prepare a double-layer structure wear-resistant coating. The medium-entropy coating is used as the base layer to avoid crack formation, and the high-entropy coating is used as the top layer to improve the wear-resistant performance of the substrate. The atomic percentage of Co, Cr, and Ni in the medium-entropy coating is 1:1:1, and the atomic percentage of Co, Cr, Fe, Ni, and Al in the high-entropy coating is 1:1:1:1:0.6/0.8/ 1.0.
Effectively avoid the cracking of coating, improve the abrasion resistance and corrosion resistance of the coating, and enhance the hardness and use performance of the substrate.
Smart Images

Figure CN119352010A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material surface modification, and in particular to a laser cladding double-layer structure wear-resistant coating and a preparation method thereof. Background Art
[0002] 316L stainless steel is a chromium-nickel austenitic stainless steel with extremely low carbon content. It has excellent oxidation resistance, corrosion resistance and high temperature resistance. Therefore, it is widely used in medical equipment, navigation, petrochemical, aviation and automobile manufacturing. However, 316L stainless steel has the disadvantages of low surface hardness and easy surface wear, which makes it easy to fail due to wear during service. This will limit its application in equipment with high wear resistance requirements. For example, in the use of aircraft engines and exhaust pipes, the consequences of small damage are also very fatal. When 316L stainless steel is used in the automotive industry, the commonly used low-alloy cold heading steel has been widely replaced by stainless steel in the fasteners of engine systems and transmission systems, and the amount is on the rise. Therefore, it is of great research significance to use coatings to improve the wear resistance of stainless steel.
[0003] The original definition of high entropy alloy is a single-phase solid solution alloy composed of five or more elements in an equimolar ratio or a near equimolar ratio. In recent years, the wear behavior of a large number of face-centered cubic (FCC) high entropy alloys has been reported, but due to the low hardness and relatively poor wear resistance of single-phase FCC high entropy alloys. In order to optimize their tribological properties, scholars have conducted some research to improve the hardness and wear properties of the alloy system, mainly involving adjusting the composition elements and microstructure of the alloy, that is, based on the tough matrix of the FCC structure, by adding Al, Ti, Mo or Nb elements to induce the precipitation of hard reinforcement phase. The presence of hard phase in the soft matrix can inhibit dislocation movement and plastic flow, thereby improving the material's resistance to deformation and enhancing wear resistance. For example: the introduction of Al elements with a large atomic radius in some single-phase FCC high entropy alloys can trigger a progressive structural change of the BCC phase.
[0004] Laser cladding technology has the advantages of a wide range of cladding material selection, small heat-affected zone, low cladding layer dilution rate, high forming accuracy, and easy automation. It is a widely used surface modification technology. However, the thermal expansion coefficient and physical and chemical properties of high-entropy coatings are quite different from those of stainless steel substrates. After cladding, cracks or even cracks are easily formed on the surface of high-entropy coatings. Summary of the invention
[0005] The present invention aims to provide a laser cladding double-layer wear-resistant coating and a preparation method thereof, which solves the problem that cracks or even cracks are easily formed on the surface of the high entropy coating after cladding due to the large difference in thermal expansion coefficient and physical and chemical properties between the high entropy coating and the stainless steel substrate.
[0006] In order to achieve the above-mentioned purpose, the technical scheme of the present invention is as follows: a laser cladding double-layer structure wear-resistant coating, the wear-resistant coating is composed of a base layer and a top layer, the base layer is a medium entropy coating, the atomic percentage of Co, Cr, and Ni spherical metal powders in the medium entropy coating is 1:1:1, and the medium entropy coating is used to avoid the formation of cracks between coatings and between coatings and substrates, and the top layer adopts a high entropy coating, and the atomic percentage of Co, Cr, Fe, Ni, and Al spherical metal powders in the high entropy coating is 1:1:1:1:0.6 / 0.8 / 1.0, and the high entropy coating is used to improve the wear resistance of the substrate.
[0007] Furthermore, the preparation method of the double-layer wear-resistant coating is as follows:
[0008] S1. Grind the stainless steel, then clean it with anhydrous ethanol and dry it for later use;
[0009] S2. Weigh Co, Cr, and Ni spherical metal powders in order according to an atomic percentage of 1:1:1, ball-mill the weighed powders, and place the processed powders in a vacuum drying oven for drying to obtain a first mixed powder;
[0010] S3, preheating the polished stainless steel substrate at a temperature of 260°C;
[0011] S4, cladding the first mixed powder on the stainless steel substrate in step S3 by using a powder feeding laser cladding technology;
[0012] S5. Weigh Co, Cr, Fe, Ni, and Al spherical metal powders in the ratio of 1:1:1:1:0.6 / 0.8 / 1.0 atomic percent, ball-mill the weighed powders, and place the processed powders in a vacuum drying oven for drying to obtain a second mixed powder;
[0013] S6. Cladding the second mixed powder onto the stainless steel substrate processed in step S4 by using powder feeding laser cladding technology.
[0014] Furthermore, the particle size of the spherical metal powder in steps S2 and S5 is 50-150 μm, and the powder purity is ≥99.9%.
[0015] Furthermore, in steps S2 and S5, the ball milling speed is 300 r / min, the ball milling time is 8 h, and the ball-to-material mass ratio is 3:1; the drying temperature of the vacuum drying oven is 80° C., and the drying time is 10 h.
[0016] Through the above settings, it is ensured that there is enough energy to melt the powder and dilute the substrate, so that there is no unmelted powder on the surface and inside of the coating, so that the coating and the substrate can achieve a good metallurgical effect.
[0017] Furthermore, in step S4, the process parameters of laser cladding are: laser power of 1.5-1.9 kW, scanning speed of 13 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon gas flow rate of 15 L / min.
[0018] Furthermore, in step S5, the process parameters of laser cladding are: laser power of 1.5-1.9 kW, scanning speed of 6 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon gas flow rate of 15 L / min.
[0019] Through the above settings, the appropriate scanning speed can make the coating thickness reach the ideal requirement. The medium entropy coating has a fast scanning speed, which can make the coating thinner and play a good connecting role as an intermediate layer. The high entropy coating has a slow scanning speed, which can make the coating thicker and have a good wear resistance. In addition, the appropriate scanning speed can make the internal structure of the coating present a uniform characteristic.
[0020] Furthermore, the thickness of the high entropy coating is 0.8-1.0 mm.
[0021] Furthermore, the thickness of the double-layer wear-resistant coating is 1.2-1.6 mm.
[0022] Compared with the prior art, this solution has the following beneficial effects:
[0023] 1. The double-layer wear-resistant coating designed in this scheme is composed of CoCrNi / Al x CoCrFeNi, where x = 0.6, 0.8, 1.0. By increasing the content of Al element in the high entropy coating, the FCC structure is promoted to transform into a larger area of the BCC structure with higher hardness, and the solid solution strengthening effect is enhanced, thereby improving the wear resistance of the coating. At the same time, the preparation method provided by this scheme adopts a laser cladding synchronous powder feeding method with low energy consumption and high material utilization. The medium entropy alloy coating is selected as the base layer because the selected material is a single soft base FCC structure, which can effectively prevent cracking between coatings and cracking between coatings and substrates, and ensure the excellent corrosion resistance of the coating. The high entropy alloy coating is selected as the top layer because the selected high entropy alloy material is a eutectic structure (FCC+BCC), and the purpose is to concentrate the BCC phase with higher hardness on the surface to increase the wear resistance of the coating.
[0024] 2. The double-layer structure coating prepared by this scheme uses a soft-based medium-entropy coating as the base layer, which effectively avoids the occurrence of coating cracking and ensures the excellent wear resistance and corrosion resistance of the coating. From a macroscopic perspective, the prepared double-layer structure coating has good cladding quality, no cracks in the coating, and excellent metallurgical bonding between the layers. From a microscopic perspective, the prepared coating has the advantages of uniform organization and dense structure.
[0025] 3. This solution adopts a powder feeding laser cladding process with perpendicular layers. In the process of preparing a double-layer structure coating, the rapid heating and cooling speed can avoid the segregation of elements and the nucleation and growth of brittle intermetallic compounds, ensuring that the coating has a stable FCC+BCC eutectic structure. Therefore, compared with the existing technology, this technology is more suitable for wear and corrosion resistance modification of material surfaces.
[0026] 4. This study studied CoCrNi / Al x Effect of Al addition on hardness and wear resistance in CoCrFeNi double-layer structure coating. The hardness gradually increases from substrate to medium entropy coating and then to high entropy coating, and this transitional increase in hardness value layer by layer avoids the problem of easy detachment between coatings. The addition of Al element will promote the formation of BCC phase of alloy solid solution and enhance the solid solution strengthening effect. The wear resistance of the three prepared double-layer structure coatings is better than that of the substrate, and it is clear that when the Al content is 1.0, the hardness of the prepared coating is as high as 434HV.
[0027] 5. CoCrNi / Al designed in this scheme x The friction coefficient of the CoCrFeNi double-layer structure coating is lower than that of the single high entropy coating AlCoCrFeNi (~0.64) and the single medium entropy coating CoCrNi (~0.70). The friction coefficients of the three double-layer structure coatings are ~0.51, ~0.42, and ~0.30, respectively. x The CoCrFeNi double-layer structure coating has better wear resistance.
[0028] 6. Compared with other processes, the composite coating prepared by this method has the advantages of high material utilization, good metallurgical quality, helping to reduce energy consumption and being green and pollution-free, and low cost. It is an advanced and environmentally friendly remanufacturing processing technology and is easier to realize industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The laser cladding CoCrNi / Al in the embodiment of the present invention x Macroscopic surface morphology of the CoCrFeNi (x = 0.6, 0.8, 1.0) double-layer wear-resistant coating;
[0030] Figure 2 Laser cladding CoCrNi / Al in the embodiment of the present invention x XRD pattern of CoCrFeNi (x = 0.6, 0.8, 1.0) double-layer wear-resistant coating;
[0031] Figure 3 The laser cladding CoCrNi / Al in the embodiment of the present invention 0.6Cross-sectional OM image of CoCrFeNi coating;
[0032] Figure 4 The laser cladding CoCrNi / Al in the embodiment of the present invention 0.8 Cross-sectional OM image of CoCrFeNi coating;
[0033] Figure 5 The laser cladding CoCrNi / Al in the embodiment of the present invention 1.0 Cross-sectional OM image of CoCrFeNi coating;
[0034] Figure 6 The laser cladding CoCrNi / Al in the embodiment of the present invention 0.6 Cross-sectional SEM image of CoCrFeNi coating;
[0035] Figure 7 The laser cladding CoCrNi / Al in the embodiment of the present invention 0.8 Cross-sectional SEM image of CoCrFeNi coating;
[0036] Figure 8 The laser cladding CoCrNi / Al in the embodiment of the present invention 1.0 Cross-sectional SEM image of CoCrFeNi coating;
[0037] Fig. 9 The laser cladding CoCrNi / Al in the embodiment of the present invention x Hardness diagram of CoCrFeNi (x=0.6, 0.8, 1.0) double-layer structure wear-resistant coating. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below through specific embodiments:
[0039] Example 1
[0040] A laser cladding double-layer wear-resistant coating, the wear-resistant coating consists of a base layer and a top layer, the base layer is a medium entropy coating with a coating thickness of 0.4 mm, the atomic percentages of Co, Cr, and Ni spherical metal powders in the medium entropy coating are 1:1:1, and the medium entropy coating is used to avoid crack formation between coatings and between coatings and a substrate, and the top layer adopts a high entropy coating with a coating thickness of 0.8 mm, the atomic percentages of Co, Cr, Fe, Ni, and Al spherical metal powders in the high entropy coating are 1:1:1:1:0.6, and the high entropy coating is used to improve the wear resistance of the substrate.
[0041] Technical principles and effects of this embodiment: The medium entropy coating has an FCC structure, and its low hardness and excellent toughness play a good role in relieving stress concentration as a base layer, inhibiting the occurrence of coating cracking. In addition, during the corrosion process, the oxidation of Cr elements in the corrosive medium can often form a dense Cr2O3 passivation film, ensuring the excellent corrosion resistance of the coating. The high entropy coating has a eutectic structure of FCC+BCC, and the presence of the hard BCC phase improves the strength and hardness of the coating. At the same time, the addition of Al elements with a large atomic radius will cause them to replace the lattice sites of other atoms, promote the formation of alloy solid solution phases, enhance the solid solution strengthening effect, and also play a role in improving the hardness and wear resistance of the coating.
[0042] The double-layer wear-resistant coating includes the following steps:
[0043] S1. Grind the 316L stainless steel with sandpaper, then clean it with anhydrous ethanol and dry it for later use.
[0044] S2. Weigh Co, Cr, and Ni spherical metal powders with a particle size distribution of 50-150 in sequence according to an atomic percentage of 1:1:1, wherein the powder purity is ≥99.9%, and put the weighed powders into a planetary ball mill for mixing, the ball mill speed is 300 r / min, the ball mill time is 8 h, and the ball-to-material mass ratio is 3:1; put the treated powder into a vacuum drying oven for drying, wherein the drying temperature is 80°C and the drying time is 10 h, to obtain a first mixed powder.
[0045] S3. Preheat three stainless steel substrates after sandpaper polishing at a temperature of 260°C.
[0046] S4. The first mixed powder is clad on the stainless steel substrate of step S3 by using powder feeding laser cladding technology. The process parameters of laser cladding are: laser power of 1.5 kW, scanning speed of 13 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon gas flow rate of 15 L / min.
[0047] S5. Weigh Co, Cr, Fe, Ni, and Al spherical metal powders with a particle size distribution of 50-150 in order according to the ratio of 1:1:1:1:0.6 atomic percentages, put the weighed powders into a planetary ball mill for mixing, the ball milling speed is 300 r / min, the ball milling time is 8 hours, and the ball-to-material mass ratio is 3:1; put the treated powders into a vacuum drying oven for drying, wherein the drying temperature is 80° C. and the drying time is 10 hours, to obtain a second mixed powder;
[0048] S6. The second mixed powder is clad on the stainless steel substrate treated in step S4 by using powder feeding laser cladding technology. The process parameters of laser cladding are: laser power of 1.5 kW, scanning speed of 6 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon gas flow rate of 15 L / min.
[0049] Fig. 9 The CoCrNi / Al prepared at a laser power of 1.5 kW 0.6 The hardness of the CoCrFeNi coating is 281HV, which is higher than the hardness of 200-210HV of most 316L stainless steels currently used in industry.
[0050] Example 2
[0051] A laser cladding double-layer wear-resistant coating, the wear-resistant coating consists of a base layer and a top layer, the base layer is a medium entropy coating with a coating thickness of 0.4 mm, the atomic percentages of Co, Cr, and Ni spherical metal powders in the medium entropy coating are 1:1:1, and the medium entropy coating is used to avoid crack formation between coatings and between coatings and a substrate, and the top layer adopts a high entropy coating with a coating thickness of 0.8 mm, the atomic percentages of Co, Cr, Fe, Ni, and Al spherical metal powders in the high entropy coating are 1:1:1:1:0.6 / 0.8 / 1.0, and the high entropy coating is used to improve the wear resistance of the substrate.
[0052] The double-layer wear-resistant coating includes the following steps:
[0053] S1. Grind the 316L stainless steel with sandpaper, then clean it with anhydrous ethanol and dry it for later use.
[0054] S2. Weigh Co, Cr, and Ni spherical metal powders with a particle size distribution of 50-150 in sequence according to an atomic percentage of 1:1:1, wherein the powder purity is 99.9%, and put the weighed powders into a planetary ball mill for mixing, the ball mill speed is 300 r / min, the ball mill time is 8 h, and the ball-to-material mass ratio is 3:1; put the treated powder into a vacuum drying oven for drying, wherein the drying temperature is 80°C and the drying time is 10 h, to obtain a first mixed powder.
[0055] S3. Preheat three stainless steel substrates after sandpaper polishing at a temperature of 260°C.
[0056] S4. The first mixed powder is clad on the stainless steel substrate of step S3 by using powder feeding laser cladding technology. The process parameters of laser cladding are: laser power of 1.7 kW, scanning speed of 13 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon flow rate of 15 L / min.
[0057] S5. Weigh Co, Cr, Fe, Ni, and Al spherical metal powders with a particle size distribution of 50-150 in order according to the ratio of 1:1:1:1:0.6 atomic percentages, put the weighed powders into a planetary ball mill for mixing, the ball milling speed is 300 r / min, the ball milling time is 8 hours, and the ball-to-material mass ratio is 3:1; put the treated powders into a vacuum drying oven for drying, wherein the drying temperature is 80° C. and the drying time is 10 hours, to obtain a second mixed powder;
[0058] S6. The second mixed powder is clad on the stainless steel substrate treated in step S4 by using powder feeding laser cladding technology. The process parameters of laser cladding are: laser power of 1.7 kW, scanning speed of 6 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon gas flow rate of 15 L / min.
[0059] Figure 1 (a) shows the CoCrNi / Al 0.6 The macroscopic surface morphology of the CoCrFeNi coating shows that the coating has good cladding quality, no cracks and good flatness;
[0060] Figure 2 CoCrNi / Al 0.6 XRD analysis of CoCrFeNi coating shows that the precipitated phase is BCC phase and the matrix phase is FCC phase;
[0061] Figure 3 and Figure 6 CoCrNi / Al 0.6 The cross-sectional OM and SEM images of the CoCrFeNi coating show that the coating changes from columnar crystals to equiaxed crystals from the bottom to the top. Both sets of images show that the sample structure is evenly distributed without cracks and pores, and the BCC hard reinforcement phase is dispersed in the structure.
[0062] Fig. 9 The CoCrNi / Al prepared at a laser power of 1.7 kW 0.6 The hardness of the CoCrFeNi coating is 295HV, which is significantly higher than the hardness of 200-210HV of most 316L stainless steel in the industry.
[0063] Example 3
[0064] A laser cladding double-layer wear-resistant coating, the wear-resistant coating consists of a base layer and a top layer, the base layer is a medium entropy coating with a coating thickness of 0.4 mm, the atomic percentages of Co, Cr, and Ni spherical metal powders in the medium entropy coating are 1:1:1, and the medium entropy coating is used to avoid crack formation between coatings and between coatings and a substrate, and the top layer adopts a high entropy coating with a coating thickness of 0.8 mm, the atomic percentages of Co, Cr, Fe, Ni, and Al spherical metal powders in the high entropy coating are 1:1:1:1:0.6, and the high entropy coating is used to improve the wear resistance of the substrate.
[0065] The double-layer wear-resistant coating includes the following steps:
[0066] S1. Grind the 316L stainless steel with sandpaper, then clean it with anhydrous ethanol and dry it for later use.
[0067] S2. Weigh Co, Cr, and Ni spherical metal powders with a particle size distribution of 50-150 in sequence according to an atomic percentage of 1:1:1, wherein the powder purity is ≥99.9%, and put the weighed powders into a planetary ball mill for mixing, the ball mill speed is 300 r / min, the ball mill time is 8 h, and the ball-to-material mass ratio is 3:1; put the treated powder into a vacuum drying oven for drying, wherein the drying temperature is 80°C and the drying time is 10 h, to obtain a first mixed powder.
[0068] S3. Preheat three stainless steel substrates after sandpaper polishing at a temperature of 260°C.
[0069] S4. The first mixed powder is clad on the stainless steel substrate of step S3 by using powder feeding laser cladding technology. The process parameters of laser cladding are: laser power of 1.9 kW, scanning speed of 13 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon flow rate of 15 L / min.
[0070] S5. Weigh Co, Cr, Fe, Ni, and Al spherical metal powders with a particle size distribution of 50-150 in order according to the ratio of 1:1:1:1:0.6 atomic percentages, put the weighed powders into a planetary ball mill for mixing, the ball milling speed is 300 r / min, the ball milling time is 8 hours, and the ball-to-material mass ratio is 3:1; put the treated powders into a vacuum drying oven for drying, wherein the drying temperature is 80° C. and the drying time is 10 hours, to obtain a second mixed powder;
[0071] S6. The second mixed powder is clad on the stainless steel substrate treated in step S4 by using powder feeding laser cladding technology. The process parameters of laser cladding are: laser power of 1.9 kW, scanning speed of 6 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon gas flow rate of 15 L / min.
[0072] Fig. 9 The CoCrNi / Al prepared at a laser power of 1.9 kW 0.6 The hardness of the CoCrFeNi coating is 265HV, which is higher than the hardness of 200-210HV of most 316L stainless steel in the industry.
[0073] By comparing the quality and hardness of the cladding layers prepared under different laser powers in Example 1, Example 2, and Example 3, the optimal process parameters for preparing a double-layer wear-resistant coating are selected in this example: laser power of 1.7 kW, scanning speed of 13 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon flow rate of 15 L / min.
[0074] Example 4
[0075] A laser cladding double-layer wear-resistant coating, the wear-resistant coating consists of a base layer and a top layer, the base layer is a medium entropy coating with a coating thickness of 0.6 mm, the atomic percentages of Co, Cr, and Ni spherical metal powders in the medium entropy coating are 1:1:1, and the medium entropy coating is used to avoid crack formation between coatings and between coatings and a substrate, and the top layer adopts a high entropy coating with a coating thickness of 0.8 mm, the atomic percentages of Co, Cr, Fe, Ni, and Al spherical metal powders in the high entropy coating are 1:1:1:1:0.8, and the high entropy coating is used to improve the wear resistance of the substrate.
[0076] The double-layer wear-resistant coating includes the following steps:
[0077] S1. Grind the 316L stainless steel with sandpaper, then clean it with anhydrous ethanol and dry it for later use.
[0078] S2. Weigh Co, Cr, and Ni spherical metal powders with a particle size distribution of 50-150 in sequence according to an atomic percentage of 1:1:1, wherein the powder purity is ≥99.9%, and put the weighed powders into a planetary ball mill for mixing, the ball mill speed is 300 r / min, the ball mill time is 8 h, and the ball-to-material mass ratio is 3:1; put the treated powder into a vacuum drying oven for drying, wherein the drying temperature is 80°C and the drying time is 10 h, to obtain a first mixed powder.
[0079] S3. Preheat three stainless steel substrates after sandpaper polishing at a temperature of 260°C.
[0080] S4. The first mixed powder is clad on the stainless steel substrate of step S3 by using powder feeding laser cladding technology. The process parameters of laser cladding are: laser power of 1.7 kW, scanning speed of 13 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon flow rate of 15 L / min.
[0081] S5. Weigh spherical metal powders of Co, Cr, Fe, Ni and Al with a particle size distribution of 50-150 in order according to the atomic percentage of 1:1:1:1:0.6 / 0.8 / 1.0, put the weighed powders into a planetary ball mill for mixing, the ball milling speed is 300 r / min, the ball milling time is 8 h, and the ball-to-material mass ratio is 3:1; put the treated powders into a vacuum drying oven for drying, wherein the drying temperature is 80° C. and the drying time is 10 h, to obtain a second mixed powder;
[0082] S6. The second mixed powder is clad on the stainless steel substrate treated in step S4 by using powder feeding laser cladding technology. The process parameters of laser cladding are: laser power of 1.7 kW, scanning speed of 6 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon gas flow rate of 15 L / min.
[0083] Figure 1 (b) shows the CoCrNi / Al 0.8 The macroscopic surface morphology of the CoCrFeNi coating shows that the coating has good cladding quality, no cracks and good flatness;
[0084] Figure 2 CoCrNi / Al 0.8 XRD analysis of CoCrFeNi coating shows that the precipitated phase is BCC phase, the matrix phase is FCC phase, and the diffraction peak of BCC phase is significantly enhanced;
[0085] Figure 4 and Figure 7 CoCrNi / Al 0.8 The cross-sectional OM and SEM images of the CoCrFeNi coating show that the coating changes from columnar crystals to equiaxed crystals from the bottom to the top. Both images show that the sample structure is evenly distributed without cracks and pores, and the BCC hard reinforcement phase distributed in the structure gradually increases.
[0086] Fig. 9 Display CoCrNi / Al 0.8 The hardness of the CoCrFeNi coating is 411 HV, which is significantly higher than that of the coating in Example 1, and is significantly higher than the hardness of 200-210 HV of most 316L stainless steels currently used in the industry.
[0087] Example 5
[0088] A laser cladding double-layer wear-resistant coating, the wear-resistant coating consists of a base layer and a top layer, the base layer is a medium entropy coating with a coating thickness of 0.6 mm, the atomic percentages of Co, Cr, and Ni spherical metal powders in the medium entropy coating are 1:1:1, and the medium entropy coating is used to avoid crack formation between coatings and between coatings and a substrate, and the top layer adopts a high entropy coating with a coating thickness of 1.0 mm, the atomic percentages of Co, Cr, Fe, Ni, and Al spherical metal powders in the high entropy coating are 1:1:1:1:1.0, and the high entropy coating is used to improve the wear resistance of the substrate.
[0089] The double-layer wear-resistant coating includes the following steps:
[0090] S1. Grind the 316L stainless steel with sandpaper, then clean it with anhydrous ethanol and dry it for later use.
[0091] S2. Weigh Co, Cr, and Ni spherical metal powders with a particle size distribution of 50-150 in sequence according to an atomic percentage of 1:1:1, wherein the powder purity is ≥99.9%, and put the weighed powders into a planetary ball mill for mixing, the ball mill speed is 300 r / min, the ball mill time is 8 h, and the ball-to-material mass ratio is 3:1; put the treated powder into a vacuum drying oven for drying, wherein the drying temperature is 80°C and the drying time is 10 h, to obtain a first mixed powder.
[0092] S3. Preheat three stainless steel substrates after sandpaper polishing at a temperature of 260°C.
[0093] S4. The first mixed powder is clad on the stainless steel substrate of step S3 by using powder feeding laser cladding technology. The process parameters of laser cladding are: laser power of 1.7 kW, scanning speed of 13 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon flow rate of 15 L / min.
[0094] S5. Weigh spherical metal powders of Co, Cr, Fe, Ni and Al with a particle size distribution of 50-150 in sequence according to the atomic percentage of 1:1:1:1:1.0, put the weighed powders into a planetary ball mill for mixing, the ball milling speed is 300 r / min, the ball milling time is 8 h, and the ball-to-material mass ratio is 3:1; put the treated powders into a vacuum drying oven for drying, wherein the drying temperature is 80° C. and the drying time is 10 h, to obtain a second mixed powder;
[0095] S6. The second mixed powder is clad on the stainless steel substrate treated in step S4 by using powder feeding laser cladding technology. The process parameters of laser cladding are: laser power of 1.7 kW, scanning speed of 6 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon gas flow rate of 15 L / min.
[0096] Figure 1 (c) shows the CoCrNi / Al 1.0 The macroscopic surface morphology of the CoCrFeNi coating shows that the coating has good cladding quality, no cracks and good flatness;
[0097] Figure 2 CoCrNi / Al 1.0 XRD analysis of CoCrFeNi coating showed that the precipitated phase was BCC phase, the matrix phase was FCC phase, and the diffraction peak intensity of the BCC phase was the strongest diffraction peak of the three coatings.
[0098] Figure 5 and Figure 8 CoCrNi / Al 1.0 The cross-sectional OM and SEM images of the CoCrFeNi coating show that the coating changes from columnar crystals to equiaxed crystals from the bottom to the top. Both sets of images show that the sample has a uniform microstructure distribution without cracks and pores, and the BCC hard reinforcement phase is the most distributed in the microstructure.
[0099] Fig. 9 Display CoCrNi / Al 1.0 The hardness of the CoCrFeNi coating is 434 HV, which is significantly higher than that of the coatings in Example 1 and Example 2, and is approximately 2.1 times the hardness of 200-210 HV of most 316L stainless steels currently used in industry.
[0100] Comparative Example 1
[0101] A method for preparing a laser cladding coating comprises the following steps:
[0102] S1. Grind the 316L stainless steel with sandpaper, then clean it with anhydrous ethanol and dry it for later use;
[0103] S2. Weigh Co, Cr, and Ni spherical metal powders with a particle size distribution of 50-150 in order according to the atomic percentage of 1:1:1, wherein the powder purity is ≥99.9%, mix the powders in a planetary ball mill, the ball milling speed is 300 r / min, the ball-to-material ratio is 3:1, and the ball milling time is 8 h. After the ball milling, put it into a vacuum drying oven for drying, the drying temperature is set to 80°C, and the drying time is 10 h to obtain a medium entropy alloy powder;
[0104] S3, the polished stainless steel substrate is preheated before laser cladding of the medium entropy coating, and the preheating temperature is 260°C;
[0105] S4. The medium entropy alloy powder is clad on the polished stainless steel substrate surface by powder feeding laser cladding. The processing parameters of laser cladding are: laser power of 1.7 kW, scanning speed of 6 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon flow rate of 15 L / min.
[0106] Comparative Example 2
[0107] A method for preparing a laser cladding coating comprises the following steps:
[0108] S1. Grind the 316L stainless steel with sandpaper, then clean it with anhydrous ethanol and dry it for later use;
[0109] S2. Weigh Co, Cr, Fe, Ni, and Al spherical metal powders with a particle size distribution of 50-150 in order according to the atomic percentage of 1:1:1:1:1, wherein the powder purity is 99.9%, mix the powders in a planetary ball mill, the ball milling speed is 300 r / min, the ball-to-material ratio is 3:1, the ball milling time is 8 h, and after the ball milling, put them into a vacuum drying oven for drying, the drying temperature is set to 80° C., and the drying time is 10 h to obtain a high entropy alloy powder;
[0110] S3, preheating the polished stainless steel substrate before laser cladding high entropy coating, the preheating temperature is 260℃;
[0111] S4. The high entropy alloy powder is clad on the polished stainless steel substrate surface by powder feeding laser cladding. The processing parameters of laser cladding are: laser power of 1.7 kW, scanning speed of 6 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon flow rate of 15 L / min.
[0112] Table 1 below shows the comparison results of the friction coefficient and wear amount between the coating and the substrate of Examples 1-5 and Comparative Examples 1 and 2.
[0113] Alloy Type Friction coefficient Wear amount / mg Example 1 0.59 8.2 Example 2 0.51 7.5 Example 3 0.62 8.9 Example 4 0.42 5.7 Example 5 0.30 4.1 Comparative Example 1 0.70 11.3 Comparative Example 2 0.64 8.7 316L Stainless Steel 0.67 10.8
[0114] By comparing Examples 1-5 with Comparative Examples 1 and 2, it can be seen that when the Al content is added to 1.0, the hardness value of the double-layer wear-resistant coating prepared is the largest and the wear resistance is the best.
[0115] In summary, the preparation method provided in this scheme promotes the large-scale transformation of the FCC structure to the BCC structure with higher hardness by changing the content of the Al element when preparing the double-layer wear-resistant coating, thereby enhancing the solid solution strengthening effect and improving the wear resistance of the coating. At the same time, a tough medium entropy coating is used as a base layer to effectively avoid the cracking of the high entropy coating caused by stress concentration, and the high entropy coating containing a hard BCC phase is used as a surface wear-resistant layer to improve the hardness, wear resistance and performance of the 316L stainless steel substrate, and ensure the safe and reliable service of the parts.
[0116] The above are only embodiments of the present invention, and the common knowledge such as the known specific structures and / or characteristics in the scheme are not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A laser cladding double-layer wear-resistant coating, characterized in that: The wear-resistant coating consists of a base layer and a top layer, the base layer is a medium entropy coating, the atomic percentage of Co, Cr, and Ni spherical metal powders in the medium entropy coating is 1:1:1, and the medium entropy coating is used to avoid the formation of cracks between coatings and between coatings and substrates, and the top layer adopts a high entropy coating, the atomic percentage of Co, Cr, Fe, Ni, and Al spherical metal powders in the high entropy coating is 1:1:1:1:0.6 / 0.8 / 1.0, and the high entropy coating is used to improve the wear resistance of the substrate.
2. The laser cladding double-layer wear-resistant coating according to claim 1, characterized in that: The preparation method of the double-layer wear-resistant coating is as follows: S1. Grind the stainless steel, then clean it with anhydrous ethanol and dry it for later use; S2. Weigh Co, Cr, and Ni spherical metal powders in order according to an atomic percentage of 1:1:1, ball-mill the weighed powders, and place the processed powders in a vacuum drying oven for drying to obtain a first mixed powder; S3, preheating the polished stainless steel substrate at a temperature of 260°C; S4, cladding the first mixed powder on the stainless steel substrate in step S3 by using a powder feeding laser cladding technology; S5. Weigh Co, Cr, Fe, Ni, and Al spherical metal powders in the ratio of 1:1:1:1:0.6 / 0.8 / 1.0 atomic percent, ball-mill the weighed powders, and place the processed powders in a vacuum drying oven for drying to obtain a second mixed powder; S6. Cladding the second mixed powder onto the stainless steel substrate processed in step S4 by using powder feeding laser cladding technology.
3. The laser cladding double-layer wear-resistant coating according to claim 2, characterized in that: The particle size of the spherical metal powder in steps S2 and S5 is 50-150 μm, and the powder purity is ≥99.9%.
4. The laser cladding double-layer wear-resistant coating according to claim 2, characterized in that: In steps S2 and S5, the ball milling speed is 300 r / min, the ball milling time is 8 h, and the ball-to-material mass ratio is 3:1; the drying temperature of the vacuum drying oven is 80° C., and the drying time is 10 h.
5. The laser cladding double-layer wear-resistant coating according to claim 2, characterized in that: In step S4, the process parameters of laser cladding are: laser power of 1.5-1.9 kW, scanning speed of 13 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon gas flow rate of 15 L / min.
6. The laser cladding double-layer wear-resistant coating according to claim 2, characterized in that: In step S5, the process parameters of laser cladding are: laser power of 1.5-1.9 kW, scanning speed of 6 mm / s, spot diameter of 3 mm, powder feeding rate of 7 g / min, and argon gas flow rate of 15 L / min.
7. The laser cladding double-layer wear-resistant coating according to claim 2, characterized in that: The thickness of the high entropy coating is 0.8-1.0 mm.
8. The laser cladding double-layer wear-resistant coating according to claim 7, characterized in that: The thickness of the double-layer wear-resistant coating is 1.2-1.6 mm.
Citation Information
Cited By
High-strength anti-cracking refractory high-entropy alloy powder, coating and application of high-strength anti-cracking refractory high-entropy alloy powder
CN120989477A
High-strength anti-cracking refractory high-entropy alloy powder, coating and application thereof
CN120989477B